Economic issues, global & national : a business perspective - Singhania, Hari Shankar (New Delhi : Vikas Pub. House, 1995)
Transcript of speeches by an Indian entrepreneur and former president, International Chamber of Commerce.
Keywords: International economic relations; India -- Commercial policy; India -- Economic policy -- 1991-.